2018
DOI: 10.31486/toj.18.0014
|View full text |Cite
|
Sign up to set email alerts
|

Role of Complementary and Alternative Medicine in Otolaryngologic Perioperative Care

Abstract: Background: During the perioperative period for otolaryngologic surgical cases, complications and delays can occur as the result of anxiety, pain, nausea, and vomiting. Conventional methods used to treat these symptoms include medications that can be expensive and invasive or that can cause adverse effects. Because of the concerns about opioid use in the United States, providers might want to consider using complementary and alternative medicine (CAM) as adjunctive or primary treatment plans. Methods: To asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…When using acetaminophen, NSAIDs, or COX inhibitors, guidelines recommend around‐the‐clock dosing, unless contraindicated, to further improve pain control . Finally, investigation into other agents or techniques, such as gamma‐aminobutyric acid agonists, ketamine, clonidine, and complementary (including cognitive behavioral therapy) and alternative medications, have been studied; however, results are mixed and future research needs to define the role of these alternative agents in the postoperative care of surgical patients …”
Section: Discussionmentioning
confidence: 99%
“…When using acetaminophen, NSAIDs, or COX inhibitors, guidelines recommend around‐the‐clock dosing, unless contraindicated, to further improve pain control . Finally, investigation into other agents or techniques, such as gamma‐aminobutyric acid agonists, ketamine, clonidine, and complementary (including cognitive behavioral therapy) and alternative medications, have been studied; however, results are mixed and future research needs to define the role of these alternative agents in the postoperative care of surgical patients …”
Section: Discussionmentioning
confidence: 99%
“…It is associated usually with mild to moderate post-operative pain. Multimodal analgesia is an effective method, to improve peri-operative analgesia with reduced dosage and limited side effects 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Only 8.7% of these patients expressed that they used a CAM method for managing their surgical illness. In a recent study, CAM usage in 11 patients who were treated with otolaryngological surgery was researched and it is reported that CAM methods were used in order to alleviate pain 14. Although there have been studies that report CAM usage contributes to quality of life (QOL) positively,7,15 it has not been specifically reported how QOL be affected in patients with RC who use any of the CAM methods.…”
mentioning
confidence: 99%
“…In a recent study, CAM usage in 11 patients who were treated with otolaryngological surgery was researched and it is reported that CAM methods were used in order to alleviate pain. 14 Although there have been studies that report CAM usage contributes to quality of life (QOL) positively, 7,15 it has not been specifically reported how QOL be affected in patients with RC who use any of the CAM methods. This study assessed preoperative CAM use rates and its effects on QOL in patients with RC who were scheduled to have surgery due to USSD.…”
mentioning
confidence: 99%